Cold War Civil Defence in Western Europe Sociotechnical Imaginaries of Survival and Preparedness - Cronqvist, Marie; Farbøl, Rosanna; Sylvest, Casper (Springer Nature, 2022)
This open access edited collection brings together established and new perspectives on Cold War civil defence in Western Europe within a common analytical framework that also facilitates comparative and transnational dimensions. The current interest in creating disaster-resilient societies demands new histories of civil defence. Historical contextualization is essential in order to understand what is at stake in preparing, devising, and implementing forms of preparedness, protection, and security that are specifically targeted at societies and citizens. Applying the concept of sociotechnical imaginaries to civil defence history, the chapters of this volume cover a range of new themes, from technology and materiality to media, memory, and everyday experience. The book underlines the social embeddedness of civil defence by detailing how it both prompted new forms of social interaction and reflected norms and visions of the 'good society' in an age where nuclear technology seemed to hold the key to both doom and salvation.